2022
DOI: 10.5644/ama2006-124.355
|View full text |Cite
|
Sign up to set email alerts
|

mcr Genes Conferring Colistin Resistance in Enterobacterales; a Five Year Overview

Abstract: <p>The present review aims to study and detect the global emergence of mcr genes in E. coli, K. pneumoniae and Salmonella spp., isolates from human specimens over the last six years. Nowadays the rise of multidrug-resistant superbugs has made essential the return of drugs that were previously abandoned. A clear example is colistin, which acts against multidrug - resistant gram - negative pathogens, including Enterobacterales. Colistin resistance is an unfortunate fact, with the emergence of mcr genes con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 44 publications
0
6
0
Order By: Relevance
“…Ten mcr homologues ( mcr -1–10) have so far been identified, and mcr-1 continues to be the main character and is widely distributed [ 10 , 11 , 12 ]. The MIC of colistin in E. coli have been shown to increase by 4 to 8-fold when the mcr-1 gene is present, indicating that mcr-1 alone can provide adequate resistance against colistin in E. coli and other Enterobacteriaceae [ 2 , 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Ten mcr homologues ( mcr -1–10) have so far been identified, and mcr-1 continues to be the main character and is widely distributed [ 10 , 11 , 12 ]. The MIC of colistin in E. coli have been shown to increase by 4 to 8-fold when the mcr-1 gene is present, indicating that mcr-1 alone can provide adequate resistance against colistin in E. coli and other Enterobacteriaceae [ 2 , 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, how M6 regulates this pathway merits further investigation. Second, the amino acid sequence of the linker domain varies among the 10 known MCR variants (S2 Fig) . Different MCR variants exhibited varying levels of colistin resistance [55,56]. Our data revealed that the catalytic domain of the MCR proteins is relatively well conserved among the MCR families (S2 Fig) , which strongly suggests that differences in the linker domain potentially govern the diverse phenotypic polymyxin resistance, an idea that will require direct experimental validation.…”
Section: Plos Biologymentioning
confidence: 73%
“…For example, unlike MCR-1, MCR-9 and MCR-10 confer poor resistance to colistin [62,63]. In fact, our was not certified by peer review) is the author/funder.…”
Section: Discussionmentioning
confidence: 99%